COST-EFFECTIVENESS ANALYSIS OF GASTRITIS THERAPY IN AN AIR FORCE HOSPITAL IN BANDUNG, INDONESIA - TANJUNG, RIANI; WARDATI, YULIA; AZIZAH, DINI NUR; PRATIWI, BHEKTI; MUSTARICHIE, RESMI; SAPTARINI, NYI MEKAR (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to analyze the cost-effectiveness of gastritis treatment and the influence factors of cost-effectiveness at an air force hospital in Bandung, West Java, Indonesia. Methods: Data were collected retrospectively from patient medical records and Hospital Information System (HIS). This study was conducted from August to October 2020. Cost data includes total costs from the perspective of the hospital (health care) and the perspective of the Social Security Administrator for Health (Badan Penyelenggara Jaminan Sosial, BPJS, payer) based on Indonesian-Case Based Groups rates. Outcomes in this study were length of stay (LOS) and leukocytes. Results: There were 129 patients in inpatient units in the year of 2018-2019. The medicines for gastritis therapy were omeprazole and ranitidine injection and lansoprazole and ulsidex tablet. The most cost-effective therapy based on LOS was ranitidine injection, while based on reducing leukocytes was, ranitidine injection from the payer's perspective and lansoprazole from healthcare perspective. Conclusion: There was no significant cost difference between the four treatment options. The sensitivity test showed that the influence factor of the Incremental Cost Effectiveness Ratio (ICER) value was decreased leukocytes.